The SDGs and inclusive education for all: From special education to addressing social inequalities - Xavier Rambla; Margarita Langthaler (Austrian Foundation for Development Research (ÖFSE), 2016)
This briefing paper draws on the recently adopted Sustainable Development Goals and the previous statements regarding inclusive education so as to propose guidelines for international aid in the area of education. Basically, both concepts stand for a wide-ranging view of education in the frame of correlative challenges and objectives. A key point is that crucial opportunities emerge from positive synergies between initiatives addressing social inequalities and catering to special needs. Four guidelines are suggested for both international donors and governments interested in ensuring inclusive, lifelong, quality education for all. The paper illustrates these general guidelines with a few observations regarding two middle-income countries as Albania and Moldova, and two low-income countries such as Burkina Faso and Ethiopia. In all of them, children and youth suffer from powerful deprivations derived from social inequalities associated to the socio-economic status of parents, gender, ethnicity and ability. In these four countries the available sources also report on shortcomings in institutional capacity that have to be urgently addressed.
Keywords: 330; Sustainable Development Goals; Inclusive Education; Education for All; Albania; Moldova; Burkina Faso; Ethiopia